Microvascular anatomy and histomorphology of extrapulmonary bronchi in adult Xenopus laevis Daudin (Lissamphibia; Anura) point to a role in aerial gas exchange - histomorphology of tissue sections and scanning electron microscopy of vascular corrosion casts - Tangphokhanon W. (Blackwell Publishing Ltd, 2014)
Studies on the amphibian respiratory tract microvascular anatomy are few. Using scanning electron microscopy (SEM) of vascular corrosion casts (VCCs) and light microscopy of perfusion-fixed tissue sections, we studied the bronchial microvascular anatomy in the adult South African Clawed Toad, Xenopus laevis Daudin. Histomorphology showed that the bronchial wall consists (from luminal to abluminal) of squamous epithelium, subepithelial capillary bed, cartilage rings or cartilage plates, a layer of dense connective tissue, a layer of smooth muscle cells, and squamous epithelium (serosa). SEM of VCCs reveals that bilaterally a ventral, a dorsal (Ø 77.21 ± 7.61 μm), and a caudal bronchial artery supply the bronchial subepithelial capillary bed. The ventral bronchial artery has 3-4 branching orders (interbranching distances: 506.3 ± 392.12 μm; branching angles of first- and second-order bifurcations: 24.60 ± 10.24° and 29.59 ± 14.3°). Casts of bronchial arteries display imprints of flow dividers and sphincters. Cranial and caudal bronchial veins (Ø 154.78 ± 49.68 μm) drain into pulmonary veins. They lack microvenous valves. The location of the dense subepithelial capillary meshwork just beneath the thin squamous bronchial epithelium and its drainage into the pulmonary veins make it likely that in Xenopus, bronchi assist in aerial gas exchange. © 2013 The Royal Swedish Academy of Sciences.